Planning nursing teaching: Educational purposes and clinical competence - Dell'Acqua, Magda Cristina Queiroz [UNESP]; Miyadahira, Ana Maria Kazue; Ide, Cilene Aparecida Costardi (FapUNIFESP (SciELO), 2009)
Thinking about nursing education implies articulating this issue with the expressions of theoretical frameworks, from the perspective of a pedagogical aspect that includes both constructivism and competencies. The objective was to characterize, from a longitudinal view, the construction of care competencies that exist in the teaching plans of nursing undergraduate programs. This exploratory-descriptive study used a qualitative approach. Documentary analysis was performed on the nine teaching plans of undergraduate care subjects. The ethical-legal aspects were guaranteed, so that data was collected only after the study had been approved by the Research Ethics Committee. The data evidenced a curriculum organization centered on subjects, maintaining internal rationales that seem to resist summative organizations. Signs emerge of hardly substantial links between any previous knowledge and the strengthening of critical judgment and clinical reasoning. As proposed, the study contributed with reconsiderations for the teachinglearning process and showed the influence of constructivism on the proposal of clinical competencies.
Keywords: Competence-based education; Education; Nursing; Professional competence; Professional practice